The role of toll-like receptors in acute and chronic lung inflammation - Qureshi Salman T; Lafferty Erin I; Schnare Markus (BMC, 2010)
Abstract By virtue of its direct contact with the environment, the lung is constantly challenged by infectious and non-infectious stimuli that necessitate a robust yet highly controlled host response coordinated by the innate and adaptive arms of the immune system. Mammalian Toll-like receptors (TLRs) function as crucial sentinels of microbial and non-infectious antigens throughout the respiratory tract and mediate host innate immunity. Selective induction of inflammatory responses to harmful environmental exposures and tolerance to innocuous antigens are required to maintain tissue homeostasis and integrity. Conversely, dysregulated innate immune responses manifest as sustained and self-perpetuating tissue damage rather than controlled tissue repair. In this article we review aspects of Toll-like receptor function that are relevant to the development of acute lung injury and chronic obstructive lung diseases as well as resistance to frequently associated microbial infections.